The Objectives of Islamic Education In The Perspective of The Tabligh Congregation In Indonesia - Irpan Irpan (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Jama'ah Tabligh is a da'wah movement that seeks to invite Muslims to return to the pure practice of Islam, with the main goal of awakening the spiritual soul in every Muslim, both personally and in social life. The Da'wah of the Jama'ah Tabligh has entered all lines, including educational institutions, therefore this article aims to explore the concept of Islamic education in the Jama'ah Tabligh group?. For this reason, the author has conducted field research with data collection techniques of participant observation, qualitative interviews, and documentation. The results of this study were found: the purpose of Islamic education in the Jama'ah Tabligh is to make a person more pious to Allah SWT, and the indicator of piety is being close to the mosque and carrying out the sunnahs of the Prophet Muhammad, and to achieve this goal one must go through the process of khuruj fii sabiilillah, and in these khuruj activities there are several programs, namely: bayan, muzakarah, deliberation, ta'lim, and jaulah. The educational goals of the Jama'ah Tabligh are in line with the national education goals of the Republic of Indonesia, Pancasila and the 1945 Constitution, and the concept of Islamic education of the Jama'ah Tabligh is in accordance with the four indicators of religious moderation issued by the Ministry of Religion of the Republic of Indonesia. and to achieve this goal, one must go through the khuruj fii sabiilillah process, and in the khuruj activities there are several programs, namely: bayan, muzakarah, deliberation, ta'lim, and jaulah. The educational goals of the Jama'ah Tabligh are in line with the national education goals of the Republic of Indonesia, Pancasila and the 1945 Constitution, and the concept of Islamic education of the Jama'ah Tabligh Jamaat is in accordance with the four indicators of religious moderation issued by the Ministry of Religion of the Republic of Indonesia. and to achieve this goal, one must go through the khuruj fii sabiilillah process, and in the khuruj activities there are several programs, namely: bayan, muzakarah, deliberation, ta'lim, and jaulah. The educational goals of the Jama'ah Tabligh is in accordance with the four indicators of religious moderation issued by the Ministry of Religion of the Republic of Indonesia.